W/O Pickering emulsion co-delivery systems stabilized by diacylglycerol nanocarriers and cellular uptake evaluation - Qiu, Chaoying; Chen, Dechu; Yu, Yasi; Lee, Yee Ying; Tan, Chin Ping; Wang, Yong (Institution of Chemical Engineers, 2026)
Lipid nanoparticulate systems are efficient as active carriers with tailorable interfacial, crystallization profiles. In this study, medium−long chain diacylglycerol (MLCD)−based solid lipid nanoparticles (SLNs) and nanostructured lipid carriers (NLCs) were constructed for curcumin (Cur) delivery to enhance its oral bioavailability and their Pickering stabilizing effects were evaluated. Cur−SLNs and NLCs stabilized by different surfactants, were prepared with particle sizes ranging from 148 to 305 nm. The nanoparticles were taken up by Caco-2 cells through clathrin and caveolae mediated endocytosis pathway, with the uptake efficiency of the NLCs being 2.25 −3.94 fold higher than that of free Cur. The nanoparticles effectively inhibited the LPS−induced inflammatory response in RAW 264.7 cells, resulting in a 60 % reduction in NO secretion. Furthermore, these SLNs/NLCs were utilized as Pickering stabilizers for water−in−oil (W/O) emulsions co−loaded with hydrophobic curcumin and hydrophilic NaCl. These emulsions demonstrated slow−release performance (78.23 −96.12 % retention) after 4 weeks storage and exhibited tunable rheological properties. The interfacial particles effectively acted as a solid shell, impeding the release of internal phase compounds. The Ritger−Peppas model offered the best fit for the release profiles of all Cur−loaded lipid formulations. This study provides a theoretical basis and technical support for the fabrication and application of lipid nanoparticles and Pickering emulsions as a multifunctional delivery system.